Extraction of chloramphenicol with organic solvents - Polonevich, Anna G.; Leschev, Sergey M.; Palianskikh, Alena I.; Belysheva, Liudmila L. (Journal of the Belarusian State University. Chemistry, 2023)
The distribution constants of chloramphenicol in the aqueous phase – organic solvent extraction systems have been experimentally determined. The relationship between the obtained values of the constants and the nature of the extraction systems phases was analysed. It has been shown that for the extraction of chloramphenicol from food products of animal origin, it is appropriate to use dichloromethane combined with salting out with ammonium sulfate. The sample preparation technique for chloramphenicol trace amounts determination with high-performance liquid chromatography with tandem mass spectrometry based on salting-out liquid-liquid extraction with dichloromethane has been developed.